Optimizing The Profit of Tartar Cake’s Slice Cakes Using Simplex Method - Vivian Bongso; Angela Velisca; Sheren Patricia; Sintia Juliawati Lestari; Dudy Effendy (Pinisi Journal of Social Science, 2024)
This research was taken from a business operating in the food and beverage industry located in the Pontianak area, West Kalimantan, precisely on Jalan Hijas, namely "Tartar Cake," This shop sells a variety of drink and dessert products with various interesting flavors. The aim of this research is to determine the profit optimization model using the simplex linear programming method. The simplex method is an approach to finding optimal solutions that have two or more decision variables. The product studied was the slice cake variant of double chocolate and double cheese which sold for IDR 20,000.00 with the decision variable being the raw material used for tartar cake. Based on the tested data, optimal results have been obtained, namely X1 = 100, X2 = 100, and Zmax = 120,000,000. This means that in one production there are 100 units of Double Chocolate Cake (X1) production and 100 units of Double Cheese Cake (X2) production which will produce a maximum profit of IDR 120,000,000.